Improving Students’ Conceptual Understanding through the Implementation of the Problem-Based Learning Model Assisted by Animated Video and Formative Assessment: A Case Study of the Diversity of Landforms in Indonesia - Kingkin Pindialesta; Akhmad Jufriadi; Qomariyah (Global Action and Education for Society, 2026)
This study aims to improve student’s conceptual understanding of the diversity of landforms in Indonesia through the implementation of the Problem Based Learning (PBL) model supported by animated videos and formative assessment. The research employed Classroom Action Research (CAR) conducted in two cycles following the Kemmis and McTaggart model, which includes planning, action, observation, and reflection stages. The participants were 28 third-grade students of SD Negeri Tanjungrejo 5. Data were collected through observation, documentation, pre-test, and post-test to measure students’ conceptual understanding. The results showed a significant improvement in students’ learning outcomes across each cycle. In the pre-cycle stage, the classical completeness rate was only 17.86%. After implementing the learning model in Cycle I, the percentage increased to 57.17%. Further improvement occurred in Cycle II, where classical completeness reached 85.71%, exceeding the predetermined success indicator. The use of animated videos helped students visualize abstract concepts of landforms, while formative assessment provided feedback on students’ understanding during the learning process. Therefore, the integration of the Problem Based Learning model, animated video media, and formative assessment proved effective in enhancing students’ conceptual understanding and creating a more active and meaningful learning environment in elementary school.